2018
DOI: 10.4149/km_2018_1_29
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characteristics of fibre laser welded joint of dual phase steel with complex phase steel

Abstract: Microstructures in the sub-zones of butt joint consisting of dual phase DP980 steel and complex phase CP780 steel with a thickness of 1.5 mm welded using fibre laser process were evaluated. The microstructure in the fusion zone was built of an approximately equal portion of martensite and lower bainite. In both coarse-grained heat affected zones near DP980 and CP780 steel dominant presence of lath martensite and a minor portion of lower bainite were observed. Similar microstructures were created in both fine-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…The mechanical properties obtained in different welding zones are a function of the microstructure. To understand the welding behavior, it is helpful to examine the microstructure of the base materials and welded joints [25,26]. Analyses of the microstructure in the fusion zone (FZ), heat-affected zone (HAZ), and base metal (BM) for all specimens were performed.…”
Section: Microstructure Characterization Of the Laser Welding Jointsmentioning
confidence: 99%
“…The mechanical properties obtained in different welding zones are a function of the microstructure. To understand the welding behavior, it is helpful to examine the microstructure of the base materials and welded joints [25,26]. Analyses of the microstructure in the fusion zone (FZ), heat-affected zone (HAZ), and base metal (BM) for all specimens were performed.…”
Section: Microstructure Characterization Of the Laser Welding Jointsmentioning
confidence: 99%
“…In recent years, the weldability [13,14] of high-strength complex phase steel, as well as the microstructure [15,16] and properties [17][18][19][20] of welded joints, have been widely investigated. M. Zhang et al [11] studied the weldability of 3.5mm thick Ti microalloyed steel CP800.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile strength of the joint was greater than 620MPa, meeting the usage requirements. X. Zhu et al [15] and P. Svec et al [16] all found the hardening of the HAZ when studying the 1mm and 1.5mm thick CP780 laser welded joints, which is related to the formation of lath martensite and bainite. Besides, P. Svec et al [16] also found a significant softening in the subcritical zone with the increase of welding heat input, which was formed by the coarsening of grains.…”
Section: Introductionmentioning
confidence: 99%
“…Fe-Zn and Zn-Al-Mg coatings are harder, more scratch resistant, have better weldability, compressibility, paintability and reduce zinc consumption compared to pure zinc coatings [7,8,9]. Weldability and formability are important characteristics of Tailored Welded Blanks for car body parts, especially when different steels are welded [10].…”
Section: Introductionmentioning
confidence: 99%